Dimensions of incidental L2 vocabulary acquisition and their effects on reading comprehension of ESL learners - Pena, Karina Dungo (Animo Repository, 2010)
This study determined incidental L2 vocabulary acquisition (IVA) through reading among samples of young ESL learners in Pampanga. The incidental research design was utilized to investigate the mental operations of the ESL participants in their acquisition of incidental L2 vocabularies and to examine the effect of IVA on their success or failure in L2 reading comprehension. This paper proposed a mediation model to decribe the interaction of prior L2 reading proficiency, receptive knowledge, and productive knowledge on incidental L2 vocabulary acquisition, L2 reading comprehension, and retention of novel words. A vocabulary checklist was used to assess the memory traces of the participants on the novel words embedded on the reading text. In addition, L2 reading comprehension test, translation, and production tasks, and recognition test were used in this study to determine their impacts on the participants incidental L2 vocabulary acquisition and retention of novel words after three weeks. Analyses reveal strong influence of prior L2 reading proficiency to receptive knowledge and productive knowledge. Furthermore, productive knowledge highly predicts L2 reading comprehension, and prior L2 reading proficiency highly predicts retention of IVA. This paper ends with recommendations for teachers, students, and school administrators.